“Now You See Me, Now You Don’t”: How Digital Consumers Manage Their Online Visibility in Game-Like Conditions - Duus, Rikke; Cooray, Mike; Lilley, Simon (Frontiers in Psychology, 2022)
Organizations continue to create digital interfaces and infrastructure that are designed to heighten consumers’ online visibility and encourage them to part with their data. The way these digital systems operate and the rules they are governed by are often opaque, leaving consumers to deploy their own strategies for managing their online information sharing with organizations. In this study, we draw upon Erving Goffman’s metaphor of expression games and three forms of concealment or cover moves to explore how consumers, who have been well socialized as digital natives, engage in dynamic and game-like interactions with organizations in an attempt to manage their level of online visibility and information sharing in relation, inter alia, to the ‘convenience’ and ‘benefits’ that are afforded to them. Our research is based on in-depth interviews in combination with photo-elicitation with 20 participants. Based on the insight generated, we offer a new framework, ‘Propensity to Game’ (P2G), which present the processual dynamics that characterize these consumers’ evolving and game-like engagements with organizations. These are Game Awareness, Rule Familiarization, Player Commitment and Game Play. Our work contributes with new insight into how these consumers actively engage in the orchestration of their online visibility by surfacing the nuanced and multifaceted decision-making and thought processes that they engage in when they, situation-by-situation, decide on the tactics and methods to use in their efforts to manage the data and information they share with organizations.